Ближе, бандерлоги!: роман / Александр Бушков - Бушков Александр Александрович (Пиранья, 2016)
Экземпляры: ф.16 (20210226) / Инвентарный номер: 60698 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Б 95 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44